Implementation of an Expert System in Diagnosing Crab Disease Using the Web-Based Certainty Factor Method - Bayu Sentosa, Rio; Maisyah Putra, Yeviki (Journal of Computer Science and Informatics Engineering, 2022)
Expert systems are a branch of artificial intelligence and are also a field of computer science that has emerged with the development of computer science today. This system works to adopt human knowledge to a computer that combines a knowledge base with an inference system to replace the function of an expert in solving a problem. In this study the type of crab that will be diagnosed is soft-cell crabs, soft cell crabs are crabs in the molting phase or soft shell crabs. Problems that arise with soka crabs in the maintenance process are due to disease factors. The emergence of disease disorders in crabs is a risk that must always be anticipated. To overcome this problem, an expert system is applied to diagnose diseases in soft-shelled crabs using the certainty factor method where from this system the public can find out about how to deal with disease problems in soft-shelled crabs and provide convenience for the community in the implementation process.